Protective effect of hydroalcoholic Rheum ribes L. extract in male rat model of lead acetate-induced nephrotoxicity - Shirin Asgharian; Hasan Hoseinkhani; Elham Bijad; Zahra Lorigooini; Mahmoud Rafieian-Kopaei (Society of Diabetic Nephropathy Prevention, 2018)
Background: In the recent years, the prevalence of metal-induced toxicity, especially leadinduced toxicity, has increased considerably. Metals including lead cause oxidative stress. Therefore Rheum ribes L. as a medicinal plant with antioxidant activity may reduce the complications of these toxicities. Objectives: The aim of the current study was to investigate the protective effect of hydroalcoholic R. ribes L. extract in male rat model of lead acetate-induced nephrotoxicity. Materials and Methods: In this experimental study, 40 male Wistar rats were randomly assigned to four groups: Normal saline (control) group, positive control group treated with 0.6 g/L/d of lead acetate in drinking water, and two R. ribes groups treated with 200 and 400 mg/kg/d of R. ribes extract in addition to lead acetate for 10 days. After treatment, the rats were anesthetized, blood samples were taken, and kidneys were removed and fixed in 10% formalin. Then, serum antioxidant capacity was measured and kidney tissue specimens histopathologically studied. Results: Serum antioxidant capacity was significantly different between lead acetate group and the group treated with lead acetate + R. ribes extract (400 mg/kg). Additionally mice receiving lead acetate + R. ribes extract (400 mg/kg) had significantly higher antioxidant capacity than the control group (P<0.05). Treatment of lead acetate-treated rats with R. ribes extract significantly prevented damage to their kidney tissues. Conclusions: Rheum ribes extract can prevent lead-induced kidney damage, and therefore exposure to lead acetate by people are recommended to consume this extract.